Trust, information quality, adverse events following immunization, and social influences as determinants of vaccination decisions: a cross-sectional study - Dorota Stefanicka – Wojtas; Agnieszka Rusiecka; Tomasz Hikawczuk; Maria Kasprzyk-Smardz; Monika Zadka; Norbert Zachara; Jarosław Zachara; Bartosz Uchmanowicz; Aneta Soll - Morka; Stanisław Manulik; Donata Kurpas (BMC Public Health, 2026)
Abstract Background Vaccination remains one of the most effective public health interventions for preventing infectious diseases. However, vaccine hesitancy continues to pose a significant challenge to the effectiveness of immunization programs. Decisions about vaccination are shaped not only by clinical or demographic factors, but also by trust in the healthcare system, the perceived quality of vaccine-related information, information source preferences, experiences with adverse events following immunization (AEFI), social influence, and attitudes toward vaccination policy. Despite growing evidence on individual determinants, studies that examine these factors simultaneously within a single analytical framework remain limited, particularly in the Central and Eastern European context. Objective This study aimed to identify psychosocial, informational, and policy-related determinants of vaccination decisions among Polish adults, with a particular focus on trust in the healthcare system, perceived availability and quality of vaccination information, information source preferences, AEFI experiences, social influence, vaccine safety concerns, and opinions on national vaccination policy. Methods A cross-sectional study was conducted among 1,224 participants, including adults, parents/legal guardians and medical personnel, recruited from primary care settings in Poland. The study population therefore comprised both adult participants reporting on their own vaccination status and parents or legal guardians reporting on behalf of their children. During logistic regression analysis and applying listwise deletion method in 44 respondents, lack of response to any of the variables used in the regression analysis resulted in their omission from the modelling. In consequence data of 1180 patients were applied in logistic regression analysis and in contingency tables with use of χ 2 Pearson’s test. Participants were classified as vaccinated ( n = 994) or non-vaccinated ( n = 186) according to the predefined study criteria. Children were classified based on adherence to the national immunization schedule. In contrast, adults were classified according to their current vaccination behavior, with individuals accepting at least one vaccination classified as vaccinated and those refusing all vaccinations classified as non-vaccinated. Data were collected using a structured questionnaire covering sociodemographic characteristics, perceived availability and quality of vaccination information, trust in the healthcare system, sources of vaccine-related information, personal and vicarious AEFI experiences, beliefs about vaccine safety, social influence, and attitudes toward vaccination policy. Differences between vaccinated and non-vaccinated groups were assessed using Pearson’s chi-squared test with calculation of odds ratios. Additionally, a logistic regression model was constructed to identify independent predictors of vaccination status. Results Significant differences between vaccinated and non-vaccinated participants were observed for place of residence ( p < 0.05) and religion ( p < 0.05). Vaccinated respondents more frequently rated the availability and quality of vaccination information as good (41.4% vs. 21.5% and 48.8% vs. 18.8%, respectively) and reported higher trust in the healthcare system ( p < 0.05). Non-vaccinated individuals were significantly more likely to use internet forums and social media as information sources (odds ratio [OR] = 3.61) and non-governmental organizations (OR = 8.75), while vaccinated participants more often relied on doctors (OR = 0.51). Vicarious AEFI experiences among family or close contacts were more frequent in the non-vaccinated group (OR = 2.50). Non-vaccinated respondents expressed greater concerns about vaccine effects on the immune system, long-term health consequences, vaccine composition, pharmaceutical industry profits, and population control. In logistic regression, significant independent predictors of vaccination status included perceived quality of vaccination information, use of the internet as an information source, use of online forums and social media, family and friends as an information source, traditional media use, family influence on vaccination decisions, and evaluation of national vaccination policy (all p < 0.05). Concerns about vaccine effects on the immune system and beliefs about pharmaceutical profits were significant negative predictors of vaccination. Conclusions Vaccination decisions in a Polish adult population are shaped by a multidimensional set of interacting factors. Perceived information quality, social media use, social influence, vaccine safety beliefs, and attitudes toward vaccination policy emerged as the most consistent independent predictors of vaccination status. These findings support the development of targeted, multi-level public health communication strategies that address information quality, digital misinformation, trust in health institutions, and community-level social norms to improve vaccination coverage. However, because of the cross-sectional design, the observed associations should not be interpreted as causal.